2015
DOI: 10.1039/c5dt01763g
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of fractional non-innocent feature of osmium coordinated 2,2′-biimidazole or 2,2′-bis(4,5-dimethylimidazole) and their interactions with anions

Abstract: Mononuclear complexes [Os(II)(bpy)2(H2L1)](ClO4)2 ([](ClO4)2) and [Os(II)(bpy)2(H2L2)](ClO4)2 ([](ClO4)2) incorporating two free NH protons at the back face of the coordinated H2L, and deprotonated L(2-) bridged symmetric dinuclear complexes [(bpy)2Os(II)(μ-L1(2-))Os(II)(bpy)2)](ClO4)2 ([](ClO4)2) and [(bpy)2Os(II)(μ-L2(2-))Os(II)(bpy)2)](ClO4)2 ([](ClO4)2) (bpy = 2,2'-bipyridine, H2L1 = 2,2'-biimidazole and H2L2 = 2,2'-bis(4,5-dimethylimidazole)) have been characterised. Crystal structures of [](ClO4)2 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 118 publications
1
37
0
Order By: Relevance
“…It was further reported that for both ruthenium(II) and osmium(II) complexes a cathodic shift of the metal related M 2+ /M 3+ oxidation was observed which is in agreement with an increased electron density due to increased σ‐donation from the ligand . More recently, the groups of Wenger and Rau reported the synthesis of 2,2′‐biimidazole and 2,2′‐bibenzimidazole complexes of iridium(III) .…”
Section: Acid–base Chemistry Of Transition Metal Bi(benz)imidazole Comentioning
confidence: 55%
See 2 more Smart Citations
“…It was further reported that for both ruthenium(II) and osmium(II) complexes a cathodic shift of the metal related M 2+ /M 3+ oxidation was observed which is in agreement with an increased electron density due to increased σ‐donation from the ligand . More recently, the groups of Wenger and Rau reported the synthesis of 2,2′‐biimidazole and 2,2′‐bibenzimidazole complexes of iridium(III) .…”
Section: Acid–base Chemistry Of Transition Metal Bi(benz)imidazole Comentioning
confidence: 55%
“… Osmium(II) coordinated 2,2′‐biimidazole complexes with anion recognition features reported by Lahiri et al …”
Section: Sensors For Small Anionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, at 0.05 T, the magnetic moment strongly decreases from 3.94 μ B (300 K) to 0.35 μ B (2 K). At this magnetic field the magnetic moment at room temperature is considerably higher than that expected for a compound containing two unpaired electrons probably due to strong spin–orbit coupling (λ) involving Os III ions (λ ≈ 3000 cm –1 ) . However, at 2 K the complex is essentially diamagnetic.…”
Section: Results and Discussionmentioning
confidence: 78%
“…On the other hand, MO compositions predict a reverse situation of metal dominated (59%) reduction with partial ligand contribution (26%) leading to the electronic structural form of [Ru II (acac) 2 (nacnac)] − (major) and [Ru III (acac) 2 (nacnac •– )] − (minor) for 1c – ( S = 0). This in effect implies the potential bidirectional (fractional) noninnocence of coordinated nacnac. , The instability of both 1c + and 1c – on the coulometric time scale has prevented us from checking their spectral features.…”
Section: Results and Discussionmentioning
confidence: 99%